La criminalité à Londres au xixe siècle : le cas des cambriolages chez les particuliers - Tri Tran (Cahiers Victoriens et Edouardiens)
During the 19th century, many Londoners had the impression of living in a dangerous city, under the constant threat of vicious and skilful criminals. The many articles published in the police press, as well as in more serious newspapers, reinforced their fear. However, official statistics tend to show that this impression was not grounded and that crime was contained by the police and the courts after the early 1840s, although the population of London was expanding. Using unpublished archives e.g. Parliamentary Papers, Home Office records, and Sessions’ Papers of the Central Criminal Court, this contribution attempts to assess the extent of robberies, the character of the criminals and their treatment by the judicial system.